Fields Watered with Blood : Critical Essays on Margaret Walker - Graham, Maryemma (Book collections on Project MUSE., 2001)
Representing an international gathering of scholars, Fields Watered with Blood constitutes the first critical assessment of the full scope of Margaret Walker's literary career. As they discuss Walker's work, including the landmark poetry collection For My People and the novel Jubilee, the contributors reveal the complex interplay of concerns and themes in Walker's writing: folklore and prophecy, place and space, history and politics, gender and race. In addition, the contributors remark on how Walker's emphases on spirituality and on dignity in her daily life make themselves felt in her writin.